Sedimentary evidence of the Late Holocene tsunami in the Shetland Islands (UK) at Loch Flugarth, northern Mainland - Engel, Max; Heß, Katharina; Dawson, Sue; Patel, Tasnim; Koutsodendris, Andreas; Vakhrameeva, Polina; Klemt, Eckehard; Kempf, Philipp; Schön, Isa; Heyvaert, Vanessa M. A. (Boreas, 2024)
Tsunami deposits around the North Sea basin are needed to assess the long-term hazard of tsunamis. Here, we present sedimentary evidence of the youngest tsunami on the Shetland Islands from Loch Flugarth, a coastal lake on northern Mainland. Three gravity cores show organic-rich background sedimentation with many sub-centimetre-scale sand layers, reflecting recurring storm overwash and a sediment source limited to the active beach and uppermost subtidal zone. A basal 13-cm-thick sand layer, dated to 426-787 cal. a CE based on 14C, 137Cs and Bayesian age-depth modelling, was found in all cores. High-resolution grain-size analysis identified four normally graded or massive sublayers with inversely graded traction carpets at the base of two sublayers. A thin organic-rich ‘mud’ drape and a ‘mud’ cap cover the two uppermost sublayers, which also contain small rip-up clasts. Grain-size distributions show a difference between the basal sand layer and the coarser and better sorted storm layers above. Multivariate statistical analysis of X-ray fluorescence core scanning data also distinguishes both sand units: Zr, Fe and Ti dominate the thick basal sand, while the thin storm layers are high in K and Si. Enriched Zr and Ti in the basal sand layer, in combination with increased magnetic susceptibility, may be related to higher heavy mineral content reflecting an additional marine sediment source below the storm-wave base that is activated by a tsunami. Based on reinterpretation of chronological data from two different published sites and the chronostratigraphy of the present study, the tsunami seems to date to c. 1400 cal. a BP. Although the source of the tsunami remains unclear, the lack of evidence for this event outside of the Shetland Islands suggests that it had a local source and was smaller than the older Storegga tsunami (8.15 cal. ka BP), which affected most of the North Sea basin.